Factors shaping policy adoption on single-use plastic bag regulation in Philippine cities and municipalities - Garcia, John Philip D. (Philippine Journal of Public Administration, 2022)
In the absence of national legislation regulating plastic bag use in the Philippines, cities and municipalities are implementing local ordinances to regulate single-use plastics. This study tested factors shaping policy adoption on single-use plastic bags in cities and municipalities, and those that would explain the variation in the type of policy adopted. Five variables were tested to generate a logistic regression model for policy adoption and a multinomial logistic regression model for policy-type variation study. These variables are waste generation, consistency in implementing solid waste management, flooding hazard, income class, and number of plastic industries. Among these factors, flooding hazard and waste generation significantly explain why LGUs are likely to adopt plastic regulation policy. While none of the factors tested could explain the choice of policy between total and partial ban, and between total ban and tax, flooding hazard significantly explained the choice of partial ban over tax.